The Effect Of Profitability, Leverage, Company Size and Company Age On Corporate Social Responsibility (CSR) Disclosures (Empirical Study of Mining Companies Listed on the IDX in 2018-2020) - Rosa Maulidyah Santi; Siti Aliyah; Moch Aminnudin (Accounting Study Program, Faculty of Economics and Business, 2022)
This study uses a quantitative type of research. The type of data used in this study is secondary data, namely data obtained indirectly through intermediary media (obtained and recorded by other parties). The population in this study were all mining companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020 and the sample was taken using a purposive sampling technique which was selected based on predetermined criteria. The method used in this research is multiple linear regression analysis method. The results in the study show that profitability has a possitive significant effect on the disclosure of Corporate Social Responsibility (CSR), Leverage has no effect on the disclosure Corporate Social Responsibility (CSR), Company Size has no effect on the disclosure Corporate Social Responsibility (CSR), and Company Age has a possitive significant effect on the disclosure Corporate Social Responsibility (CSR)